Outcomes of Dynamic Condylar Screw Fixation in the Management of Distal Femur Fractures (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Distal femur fractures constitute a small but challenging group of injuries that demand precise fixation for optimal recovery. The dynamic condylar screw (DCS) system provides angular stability and allows controlled compression at the fracture site.Objective: This study aimed to evaluate the clinical and radiological outcomes of DCS fixation in patients with distal femur fractures treated at a tertiary care hospital.Methods: A prospective study was conducted on 26 patients diagnosed radiographically with distal femur fractures and managed surgically using dynamic condylar screw fixation between January and December 2022. Patients aged 20–65 years were included. Postoperative progress, union rate, and functional outcomes were assessed both clinically and radiographically.Results: Of the 26 patients, 76.9% were males and 23.1% females. The majority (46.15%) were aged 41–60 years. The average operative time was 78 ± 6.15 minutes, and the mean hospital stay was 8.5 ± 2.5 days. Complications included one nonunion, two superficial infections, and one implant failure. Based on Neer’s criteria, the final outcomes were excellent in 61.54%, good in 23.07%, fair in 11.54%, and poor in 3.85% of cases. The overall union rate was 94.84%, with a range of motion between 10° and 130°.Conclusion: Dynamic condylar screw fixation offers reliable results with excellent union rates and functional recovery when performed with proper surgical expertise. It remains an effective method for managing distal femur fractures, especially in settings with limited resources.J Shaheed Suhrawardy Med Coll 2024; 16(2): 20-23